2017
DOI: 10.1038/s41598-017-03677-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential synchrotron X-ray imaging markers based on the renal microvasculature for tubulointerstitial lesions and glomerulopathy

Abstract: High resolution synchrotron microtomography capable of revealing microvessels in three dimensional (3D) establishes distinct imaging markers of mouse kidney disease strongly associated to renal tubulointerstitial (TI) lesions and glomerulopathy. Two complementary mouse models of chronic kidney disease (CKD), unilateral ureteral obstruction (UUO) and focal segmental glomerulosclerosis (FSGS), were used and five candidates of unique 3D imaging markers were identified. Our characterization to differentially refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Micro-CT is highly reproducible and is believed to be a reliable approach in preclinical and basic kidney researches, especially useful in vasculature-related kidney pathologies such as renal fibrosis (Hlushchuk et al, 2018). In this study, it was obviously observed that unilateral ureteral obstruction mice had dramatic loss of microvessels in fibrotic kidneys compared with the sham mice by micro-CT, showing reduction in numbers of blood vessels and vessel branching, and decrease in vessel tortuosity in the left kidneys, which were in line with Ehling et al, 2016 andLin et al, 2017. And shenkang injection alleviated loss of micro-vessels, showing obvious increases in numbers of blood vessels, vessel branching, and vessel tortuosity.…”
Section: Discussionsupporting
confidence: 74%
“…Micro-CT is highly reproducible and is believed to be a reliable approach in preclinical and basic kidney researches, especially useful in vasculature-related kidney pathologies such as renal fibrosis (Hlushchuk et al, 2018). In this study, it was obviously observed that unilateral ureteral obstruction mice had dramatic loss of microvessels in fibrotic kidneys compared with the sham mice by micro-CT, showing reduction in numbers of blood vessels and vessel branching, and decrease in vessel tortuosity in the left kidneys, which were in line with Ehling et al, 2016 andLin et al, 2017. And shenkang injection alleviated loss of micro-vessels, showing obvious increases in numbers of blood vessels, vessel branching, and vessel tortuosity.…”
Section: Discussionsupporting
confidence: 74%
“…8). The sensitivity of this metric is particularly relevant to the model of focal segmental glomerulosclerosis (Adriamycin nephropathy), where podocyte injury is highly varied across glomeruli (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…We expect that NR can be applied to process fluorescence images taken by super-resolution microscopy and expansion microscopy with resolution beyond the optical limit (Small and Stahlheber, 2014;Sigal et al, 2015). Also, the concept of an HDR thresholding mask is likely applicable for identifying other tree-like structures, such as tracheoles and blood vessels (Lin et al, 2017), or other types of non-fluorescent images, such as X-ray images (Ng et al, 2016). With automated NR for high-throughput single-neuron segmentation, connectome mapping for large brains with billions of neurons is now conceivable.…”
Section: Discussionmentioning
confidence: 99%